2023
DOI: 10.29333/iji.2023.16111a
|View full text |Cite
|
Sign up to set email alerts
|

An Active Learning Study: Mastering Music Coordination Skills through Kompang and Dalcroze Eurhythmics among Primary Students

Abstract: Music coordination skill is very important in music education and performance. A problem that has been identified is that children are unable to sing and play traditional percussion (kompang) simultaneously during school music performance. It appears that the necessary skill is barely coached with the current teaching methods used by primary school teachers. This not only affects performance quality but also necessitates more hours of training despite students being talented in singing or playing musical instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Many studies have been conducted to identify appropriate educational tools for students with special needs. For example (Ismail et al, 2023) Investigate the possible approaches that could help music students avoid the complexity of singing and playing traditional percussion (kompang) simultaneously during school music performances, his study found that Dalcroze's approach is able to speed up and ease students' mastery of musical skills compared to the conventional methods used, by adopting this approach, students were able to master singing skills while playing kompang.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies have been conducted to identify appropriate educational tools for students with special needs. For example (Ismail et al, 2023) Investigate the possible approaches that could help music students avoid the complexity of singing and playing traditional percussion (kompang) simultaneously during school music performances, his study found that Dalcroze's approach is able to speed up and ease students' mastery of musical skills compared to the conventional methods used, by adopting this approach, students were able to master singing skills while playing kompang.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Singing has gained popularity as an educational activity inside schools due to its potential to enhance students' learning, skill refinement, and overall development, including several aspects such as coordination, social interaction, cognitive abilities, emotional well-being, and motor sensorimotor skills (Ismail et al, 2023;Sa'aid et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%